At the Interface of Materials Science and Clinical Care: Transforming Treatments and Procedures in Health - Luiz Fernando Cotica (Journal of Digital Health and Advanced Biomaterials, 2026)
The convergence of materials science, digital health, and computational technologies is progressively transforming the way healthcare treatments and procedures are developed, evaluated, delivered, and monitored. Building on the scientific foundations established by contributions already published by JDHAB, this editorial advances the discussion from technological validation toward clinical translation. Advanced biomaterials, biosensors, artificial intelligence, computational modeling, and digital traceability are creating new possibilities for integrating material performance, biological response, and clinical decision-making. The central premise remains unchanged: technological innovation acquires scientific and clinical value only when supported by methodological rigor, transparent measurement, reproducibility, and meaningful applicability to patient care.